Identification of MicroRNA Targets of Capsicum spp. Using MiRTrans—a Trans-Omics Approach - Zhang, Lu; Qin, Cheng; Mei, Junpu; Chen, Xiaocui; Wu, Zhiming; Luo, Xirong; Cheng, Jiaowen; Tang, Xiangqun; Hu, Kailin; Li, Shuai C. (Frontiers in Plant Science, 2017)
The microRNA (miRNA) can regulate the transcripts that are involved in eukaryotic cell proliferation, differentiation, and metabolism. Especially for plants, our understanding of miRNA targets, is still limited. Early attempts of prediction on sequence alignments have been plagued by enormous false positives. It is helpful to improve target prediction specificity by incorporating the other data sources such as the dependency between miRNA and transcript expression or even cleaved transcripts by miRNA regulations, which are referred to as trans-omics data. In this paper, we developed MiRTrans (Prediction of MicroRNA targets by Trans-omics data) to explore miRNA targets by incorporating miRNA sequencing, transcriptome sequencing and degradome sequencing. MiRTrans consisted of three major steps. First, the target transcripts of miRNAs were predicted by scrutinizing their sequence characteristics as an initial potential targets pool. Second, false positive targets were eliminated if the expression of miRNA and its targets weakly correlated by lasso regression. Third, degradome sequencing was utilized to capture the underlying miRNA targets by examining the cleaved transcripts. Finally, the predicted targets from the second and third step were combined by Fisher’s combination test. MiRTrans was applied to identify the miRNA targets for Capsicum spp. (i.e. pepper). It can generate more functional miRNA targets than sequence-based predictions in terms of functional enrichment. MiRTrans identified 58 miRNA-mRNA pairs with high confidence from 18 miRNAs families conserved in eudicots. Most of these targets were transcription factors; this lent support to the role of miRNA as key regulator in pepper. To our best knowledge, this work was the first attempt to investigate the miRNA targets of pepper, as well as their regulatory networks. Surprisingly, only a small proportion of miRNA-mRNA pairs were shared between degradome sequencing and expression dependency predictions, suggesting that miRNA target predicted from a single technology alone may be prone to report false negatives.